Kemajuan Teknologi Dan Siasat Untuk Berkembang - Ign. Hening Swasono (Ars: Jurnal Seni Rupa dan Desain, 2011)
Technology Advance and Its Development Strategy. Art education organized by the Faculty of  Visual Art of  ISI Yogyakarta is related to the dynamic of  the art development in the visual art practitioners’ networking in both national and global level. The students enrich their knowledge and experience from inside as well as outside the campus by employing various strategies. Within this process, at many times the effort in achieving an artistic convention crashes with the artistic creativity that develops along with the world improvement. Market undeniably has to be considered in assisting the students to be ‘mature’ artists. It is also a must that art interacts with other fields of  science. Technology will hold an important position as new learning resources in the education of  art.Keywords: interdisciplinary, art, new technology, art education institution, art world